THE ROLE OF LENDING IN ACHIEVING ECONOMIC DEVELOPMENT (THE AGRICULTURAL SECTOR AS A MODEL) - Maather Timol Shebl (Scholar Express Journals, 2022)
The research aims to identify the problems that agricultural projects in Iraq are suffering from, with an indication of the centrality of funding for these projects, as well as tracking financing methods and methods in order to raise the productive capacities of these projects. A number of topics were addressed, the most important of which were the definition of small agricultural projects and their characteristics and factors affecting them, financing services for small agricultural projects, the policy of agricultural financing and lending and their role in developing agriculture in Iraq, as well as the problems and obstacles facing agricultural financing. The research reached a set of conclusions, the most important of which was the weakness of the supervisory role of financial control over banking performance, which in turn led to the weakness of administrative control contributing to correcting the trend, and the absence of prediction of difficulties and obstacles, evaluating the performance of managers and ensuring their efficiency and behavior, as well as the Ministry of Agriculture importing production inputs and providing them to producers. farmers, in a fair and affordable way
Keywords: agricultural projects; production; providing; farmers